Análise jurídico-institucional dos investimentos estrangeiros na produção de petróleo e gás, de acordo com o disposto na Ordem Econômica e Financeira da Constituição da República, visando à construção de um quadro normativo que propicie condições de segurança para a realização destes investimentos no Brasil - Awazu, Luís Alberto de Fischer (2017)
The main objective of this thesis is to analyze mechanisms to stimulate the study of legal certainty in the face of the practical application of the principle of legal certainty in cases of foreign direct investment in oil and gas in Brazil, under the provisions of Chapter 1 of Title VII of the Federal Constitution of the Republic of Brazil called "General Principles of Economic Activity", mainly in the face of regulatory or institutional risk. For this reason Chapter 1 also contemplates the discipline of foreign capital (art. 172), state intervention in the economic domain (articles 173 and 174) and legal discipline of oil extraction (art. 177). In fact, the present study focuses on the constitutional law applied to concrete cases, in order to allow the various constitutional principles that make up the economic constitution to be verified when applied to foreign investments, mainly as a result of the State's regulatory activity. In addition with the study of the legal dispositions related to the matter, we must relate its application with the principle of legal certainty. This constitutes a metavalue, essential to constitutional law. Therefore, one of the major challenges of this research is the identification of parameters for an effort to apply this principle, that is, its application to concrete legal relationships. In this sense, the specific regulations of the oil and gas sector and foreign investment in Brazil were analyzed. Afterwards, new parameters were proposed related regulation of economic activity, such as the proposal of new principles of state performance and the adoption of mechanisms of public governance. In addition, it is proposed mechanisms for the preservation of contracts in force with the State and the analysis of parameters of the control of administrative discretion, in cases in which the authorizing legal command has low normative density, with a view to meeting the principle of legality in a concrete case. Finally, ponctual regulatory measures are proposed in order to promote legal certainty in the application of the constitutionally adequate ideology regarding foreign direct investment and the oil and gas industry